Liquid‐Crystalline Soft Actuators with Switchable Thermal Reprogrammability. Issue 12 (4th February 2020) - Wu, Yahe; Yang, Yang; Qian, Xiaojie; Chen, Qiaomei; Wei, Yen; Ji, Yan
Abstract: Thermal reprogrammability is essential for new‐generation large dry soft actuators, but the realization sacrifices the favored actuation performance. The contradiction between thermal reprogrammability and stability hampers efforts to design high‐performance soft actuators to be robust and thermally adaptable. Now, a strategy has been developed that relies on repeatedly switching on/off thermal reprogrammability in liquid‐crystalline elastomer (LCE) actuators to resolve this problem. By post‐synthesis swelling, a latent siloxane exchange reaction can be induced in the common siloxane LCEs (switching on), enabling reprogramming into on‐demand 3D‐shaped actuators; by switching off the dynamic network by heating, actuation stability is guaranteed even at high temperature (180 °C). Using partially black‐ink‐patterned LCEs, selectively switching off reprogrammability allows integration of completely different actuation modes in one monolithic actuator for more delicate and elaborate tasks. Abstract : The old switcheroo : Soft actuators with switchable thermal reprogrammability have been developed. By flexibly switching on/off network dynamics, easy reprogramming and excellent actuation stability can be achieved, as well as efficient recycling and seamless integration of different motions in a very common siloxane liquid crystalline elastomer.